Pengaruh Capital Intensity, Pertumbuhan Penjualan, dan Leverage Terhadap Tax Avoidance - Azri Syifa; Rananda Septanta (CV. ITTC INDONESIA, 2024)
This research aims to determine the effect of capital intensity, sales growth and leverage on tax avoidance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The type of research used is quantitative research using secondary data obtained from www.idx.co.id and the websites of each company. The population in this research are food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sample used in this research was 23 companies with an observation period of 5 years in the 2018-2022 period and the number of financial reports sampled in this research was 115. The analytical tool used in this research was analysis with the help of the eviews version 10 program. Results The research conducted shows that simultaneously capital intensity, sales growth and leverage influence tax avoidance. while partially capital intensity has no effect on tax avoidance, partially sales growth has an effect on tax avoidance, and partially shows that leverage has an effect on tax avoidance.